Emotional Intelligence and Values in Digital World through Emoticons among Indian Students and Faculty - Bhuvaneswari G; Subhasri Vijayakumar (International Journal of Asian Education, 2021)
This study aims to striking differences between emotions in the real world, and emoticons of the digital world are the key focus areas as emotions play a crucial role in communication. It is undeniable that the emoticons of the digital world have changed altogether the way language is being perceived. This study also insists that while teaching time management and soft skills to students, it is vital to teaching digital communication (expressions via online). Therefore, it may need to be stressed in the curriculum. Conversation analysis or 'talk-in-interaction, a communication strategy, insists that everyday conversations have significance on the initiator—the method using the Emotional and Social Competency Inventory (ESCI) to get the analysis done. The results confirm a significant relationship between emotional intelligence (particularly on the clusters of self-management, social awareness, and relationship management) and communication skills.